Research on power-load matching dispatching of Hydro-Wind-PV hybrid system in cascade. Issue 1 (1st February 2023) - Liu, Fang; Wang, Yunling; Su, Yunche; Xu, Ke; Chen, Wei; He, Xingqi; Wu, Gang; Ju, Chengqian
Abstract: With the goal of "double carbon, " wind power and PV are connected to the grid on a large scale, which poses a great challenge to the safe operation of the grid. The synergistic optimization of "hydro-wind-PV hybrid systems" can bring into play the ability of coordination and mutual assistance between different types of power sources, which is one of the important measures to increase the safe operation of the power grid and reduce abandoned wind and photovoltaic power. Based on the analysis of the characteristics of hydro-wind-PV power, the "hydro-wind-PV" integrated network-source cooperative optimization scheduling model is constructed to maximize the source-load matching and the consumption of clean energy. Finally, the results of a case study of a hydropower-wind power-photovoltaic cluster project in southwest China are used to verify the rationality and feasibility of the model.